The dynamics of dissociative chemisorption of H2 on a Si(111) surface - Ibrahim Ali , Noorbatcha; B.M., Rice; D.L., Thompson; L.M., Raff (American Institute of Physics (AIP), 1987)
The dissociativechemisorption and scattering of H2 on an unreconstructed Si(111) surface has been investigated using classical trajectories on a potential‐energy surface previously used to study H2 recombination/desorption from Si(111) [J. Chem. Phys. 8 5, 3081 (1986)]. The results show H2scattering from Si(111) to be elastic and predominately specular. The scattered translational energy distributions are broadened but there is virtually no change in the average values. There is very little energy transfer to or from the internal H2 modes. Lower limits to sticking probabilities are obtained as a function of the temperature. Adsorption of H2 is found to always involve dissociation and subsequent chemisorption of both hydrogen atoms. The reaction exothermicity for chemisorption is primarily deposited into vibrational motion of the newly formed Si–H bonds.Energy transfer out of these bonds into the phonon modes of the lattice is a rapid, first‐order process whose rate decreases with increasing surface temperature. Hydrogen atom mobilities on the surface computed from the velocity autocorrelation function are found to decrease rapidly with increasing residence time on the surface due to energy transfer to the lattice. Thermal diffusion of hydrogen atoms on the Si(111) surface is a slow process with a high activation energy.